THE INCREASING EMPHASIS ON ACCOUNTING AS A SOCIAL FORCE. - Grady, Paul (The Accounting Review, 1948)
Against the extensive background of history it is of great interest to note the comparatively recent origins of two phenomena which people regard as outstanding characteristics of Western Civilization. The author refer to the establishment of responsible parliamentary government since the last quarter of the Seventeenth Century, less than three hundred years ago, and to the development of the industrial system of economy since the last quarter of the Eighteenth Century, less than two hundred years ago. The author is certain that accounting, even though elementary in method, served useful purposes in the governmental and economic undertakings through all the millenniums encompassed by the identifiable civilizations. However, an art or science cannot become a social force until the economic and governmental conditions permit an independent professional development which may then use its talent in making a contribution to the public welfare. These favorable conditions for the field of accounting did not arise until after the establishment of responsible representative government and an industrialized economy. As industrialization progressed business enterprises attained much wider scope and transactions became more and more complex. Under these conditions the proprietors found it necessary to divide duties among personnel in accord with the logical phases of the activities and to base judgment to a greater and greater extent upon facts and interpretations furnished by the accounting process.